Extraction of SiO2 and Al2O3 from coal gangue activated by supercritical water. (1st October 2019) - Han, Lina; Ren, Weiguo; Wang, Bing; He, Xingxing; Ma, Lingjun; Huo, Qihuang; Wang, Jiancheng; Bao, Weiren; Chang, Liping
Graphical abstract: Highlights: Natural coal gangue is activated by alkaline supercritical water (SCW). It can be converted to mesoporous SiO2 by subsequent HCl leaching and Al2 O3 by adding NaOH and CO2 . The as-synthesized SiO2 has high BET specific surface area of 710 m 2 ·g −1 with pore diameter range 2–8 nm. The modified SiO2 shows good absorption capacity for xylene. Abstract: In this work, a novel method is introduced to activate coal gangue (CG) for extraction of Si and Al species. The activation experiments were carried out using a stainless steel tube reactor (17 mL) and an autoclave reactor (1000 mL). Firstly, CG was activated by supercritical water added with alkali. It was found that the kaolinite phase of raw CG could be transformed into cancrinite, sodalite and kalsilite by using NaOH, Na2 CO3 and KOH as activators, respectively. Secondly, silica (SiO2 ) and alumina (Al2 O3 ) were prepared by acid and alkali combination method. The extraction rates of Al 3+ and Si 4+ from the activated CG using KOH as activator were as high as 78.9% and 69.2%, respectively. The purity of SiO2 and Al2 O3 products were 96.2% and 99.3%, respectively. The as-synthesized SiO2 both from 17 mL and 1000 mL reactor exhibited very high specific surface areas of 710.0 m 2 ·g −1 and 872.8 m 2 ·g −1, respectively. In addition, the SiO2 after hydrophobic modification displayed excellent absorption selectivity for xylene.